2012
DOI: 10.1371/journal.pone.0040874
|View full text |Cite
|
Sign up to set email alerts
|

GLI2 Regulates TGF-β1 in Human CD4+ T Cells: Implications in Cancer and HIV Pathogenesis

Abstract: Elevated levels of the immunoregulatory cytokine TGF-β1 in cancer and HIV infection have been linked to the suppression of protective immune responses. The transcriptional regulation of TGF-β1 is complex and still not completely understood. We report here for the first time that the transcription factor GLI2 regulates the expression of TGF-β1 in human CD4+ T cells. In silico screening revealed five novel putative GLI binding sites in the human TGF-β1 promoter. At least two of these sites within the human TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…In this tumor, as well as in one HCC tumor, we detected HBV S protein transcripts integrated into GLI2, generally considered a marker of activation of the sonic hedgehog signaling pathway, which has been shown to play a role in aggressive types of renal cell carcinoma (30)(31)(32) and in HCC (33,34).…”
Section: Resultsmentioning
confidence: 93%
“…In this tumor, as well as in one HCC tumor, we detected HBV S protein transcripts integrated into GLI2, generally considered a marker of activation of the sonic hedgehog signaling pathway, which has been shown to play a role in aggressive types of renal cell carcinoma (30)(31)(32) and in HCC (33,34).…”
Section: Resultsmentioning
confidence: 93%
“…In one case, GLI2 was found to regulate the expression of TGFβ1 in human CD4+ cells. Researchers have shown the presence of GLI2-binding sites in the TGFβ1 promoter in CD4+ cells [76] . Reporter and ChIP assays showed that GLI2 was able to bind to two of these sites to promote transcriptional activation of TGFβ1 [76] .…”
Section: Gli2 and Disease: Congenital Malformations And Cancermentioning
confidence: 99%
“…Researchers have shown the presence of GLI2-binding sites in the TGFβ1 promoter in CD4+ cells [76] . Reporter and ChIP assays showed that GLI2 was able to bind to two of these sites to promote transcriptional activation of TGFβ1 [76] . Since regulatory T cells are associated with a poor prognosis in many tumors, understanding their regulation and function for the purposes of aiding in cancer therapy may be important.…”
Section: Gli2 and Disease: Congenital Malformations And Cancermentioning
confidence: 99%
“…Previous studies have shown that GLI2 can modulate the expression of TGF-β(28). Furthermore, we have shown that GLI2 modulates the expression and secretion of IL-6 and IL-6R(4, 29).…”
Section: Discussionmentioning
confidence: 99%